COMPETENCY DEVELOPMENT FOR THE HEADMASTER OF MADRASAH ALIYAH NU 04 AL MA'ARIF BOJA, KENDAL REGENCY - Kiswoyo, Kiswoyo (Universitas Negeri Semarang, 2021)
Pembinaan ini merupakan pengabdian kepada masyarakat yang bertujuan memberi sosialisasi mengenai kompetensi Kepala Madrasah Aliyah NU 04 Al Ma'arif Boja Kabupaten Kendal. Kompetensi Kepala Madrasah Aliyah pada saat ini harus menggunakan ketentuan Menteri Agama RI Nomor 24 Tahun 2018. Pembinaan sosialisasi ini ditujukan kepada peserta yang terdiri dari para calon Kepala Madrasah Aliyah, semua Guru dan panitia recruitment serta pengurus Badan Pelaksana Penyelenggara Pendidikan Ma’Arif NU (BP3MNU). Dengan sosialisasi ini diharapkan semua peserta memahami ketentuan tersebut, sehingga proses recruitment yang akan dilakukan dapat berjalan sesuai dengan ketentuan. Pembinaan ini berhasil memberi kesamaan persepsi dari semua peserta, sehingga dapat mempermudah pelaksanaan. Hasil dari pembinaan dengan sosialisasi ini mampu dipahami dengan baik oleh semua peserta, hal ini dapat mewujudkan kompetensi Kepala Madrasah Aliyah yang diharapkan semua pemangku kepentingan. This development is a community service that aims to provide socialization about the competence of the Head of Madrasah Aliyah NU 04 Al Ma'arif Boja Kendal Regency. The competence of the Head of Madrasah Aliyah at this time must use the provisions of the Minister of Religious Affairs of the Republic of Indonesia Number 24 of 2018. The socialization development was aimed at participants consisting of the candidates of the Head of Madrasah Aliyah, all teachers and the recruitment committee as well as the board of executives of the Education Organizing Board Ma'arif NU (BP3MNU). With this socialization, it is expected that all participants understand the provisions, so that the recruitment process that will be carried out can run in accordance with the provisions. This coaching managed to give the common perception of all participants, so as to facilitate the implementation. The result of coaching with this socialization is able to be well understood by all participants, it can realize the competence of the Head of Madrasah Aliyah that is expected by all stakeholders.